The Concept of Terrorism and the Iraqi Legislation Position (comparative Study) (Al-Mansour Journal, 2022)
The research examines whether there is a unified definition towards terrorism that can be capable to identify exactly what terrorism is, and reflect such definition towards the Iraqi anti-terrorism law enacted in 2005. The research has explored that whether the Iraqi legislator has succeeded in defining terrorism in the new enacted legislation. The research has concluded that the problem exists in the global and national conflict towards the accurate definition towards the acts of terrorism, which has caused the change of terrorism meaning in various history stages, such result has generated the impossibility to stand on one definition. Therefore the Iraqi legislator has followed the paths that have been implemented in other legislative experiences all over the world in defining terrorism.The difficulty in finding a unified definition to terrorism has emerged a difficulty in finding an accurate legal criterion, to solve such problem and in order to remedy such lack of legal criterion the research has concluded that a more developed process toward observing the process of the judicial system involved in terrorism cases must be applied, in addition the employment of new technologies that can be effective in exposing the accurate evidence and that the accused has definitely has committed such salvage crimes is essential.
Keywords: Definition of Terrorism; counterterrorism; Iraqi law